Shariah Rulings of Residence in Non-Muslim Societies: An Exploratory Review: غیر مسلم معاشروں میں رہائش کا شرعی حکم : ایک تحقیقی جائزہ - Shafi, Muhammad; Ahmed, Dr. Munir (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Scholars have given different opinions about living in non-Muslim societies. Islamic jurisprudence and various situations are taken into account while considering this topic. However, essence of this topic is that the Muslim should not face any predicament in his religion, faith, worship, and other important matters of life. If a Muslim dwells in a non-Muslim community and there are no impediments for him to practice his religion, such as freedom of worship, association with co-religionists, and protection of his rights, then residence is permitted in such a state. The most crucial thing is that a Muslim should have the freedom to live according to his religion. If a Muslim faces impediments in his religion, worship, or social rights, then it is not pertinent to live in such a place. If there is a Muslim community in a non-Muslim country and they are trying to practice their religion freely, it may be easier to live there, provided the Muslim is not alone or isolated there. Some scholars argue that if living in a non-Muslim country causes problems for Muslims in terms of religion and world, such as weakness in faith, aloofness from religious teaching, or social corruption, then it is not permissible to live there. Another crucial question is whether they are living under a non- Muslim rule, such as a non-Muslim government. If their rights are protected and they enjoy freedom in this rule, then there is justification for residence, provided that Muslims are free to practice their religion there. As a result, if the offspring of a Muslim may be religiously weak or she may be distant from religion, so this may also be a cause for concern. If a person can live in a non-Muslim country and practice his religion, it may be permissible for him to stay there. However, if there is any danger or hardship related to religion, then staying in such a place is not only permissible but also undesirable. Nowadays, Muslim residents of many Muslim countries are moving to non-Muslim countries. The purposes of going are different. There is a need for a Shariah review of traveling to non-Muslim societies and staying there. Under this requirement, the article under review is being written.